2015
DOI: 10.7775/rac.es.v83.i3.5940
|View full text |Cite
|
Sign up to set email alerts
|

Tabaquismo en médicos de la República Argentina II. Estudio TAMARA II

Abstract: Introducción: El tabaquismo es la principal causa de morbimortalidad evitable, por lo que es importante conocer las características del tabaquismo en los médicos y su actitud con los pacientes fumadores. Objetivo: Investigar la prevalencia de tabaquismo en médicos de la Argentina, los factores asociados con su consumo y la conducta frente a sus pacientes fumadores. Material y métodos: Estudio observacional y transversal de médicos de distintas especialidades de la Argentina, realizado entre junio y diciembre d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
17

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 3 publications
0
6
1
17
Order By: Relevance
“…The smoking rate reported in this study is lower than that reported in previous studies of 20% to 35% prevalence among physicians in Argentina (Gigliotti et al, 2013; Minervini et al, 2006; Tambussi et al, 2003; Zabert et al, 2005; Zylbersztejn et al, 2007). Our finding of a lower prevalence may be explained by selection bias of the sample studied because physicians had to sign an informed consent to participate in research that included randomization to a follow-up educational intervention.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…The smoking rate reported in this study is lower than that reported in previous studies of 20% to 35% prevalence among physicians in Argentina (Gigliotti et al, 2013; Minervini et al, 2006; Tambussi et al, 2003; Zabert et al, 2005; Zylbersztejn et al, 2007). Our finding of a lower prevalence may be explained by selection bias of the sample studied because physicians had to sign an informed consent to participate in research that included randomization to a follow-up educational intervention.…”
Section: Discussioncontrasting
confidence: 78%
“…Physicians have an important potential role in the implementation of smoking cessation interventions even though the prevalence of tobacco use among physicians and medical students in Argentina has been similar to that of the general population in previous surveys (Gigliotti et al, 2013; Mejia, Martinez, Gregorich, & Perez-Stable, 2010; Tambussi, Schoj, Perel, Zabert, & Ortiz, 2003; G. Zabert, Chatkin, & Ponciano-Rodriguez, 2010; G Zabert&Verra,2004; G Zabert, Videla, & Verra, 2005; Zylbersztejn et al, 2007). …”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, such prevalence is lower than that reported for Argentine medicine students and medical practitioners. The F.U.M.Ar study, 13 conducted in 2004 in 12 schools of medicine in Argentina, estimated a smoking prevalence of 35.2% among students, while the TAMARA study 14 reported a prevalence of 30.2% in a sample of almost 6500 Argentine physicians.…”
Section: Discussionmentioning
confidence: 99%